Improved gas heaters for supercritical CO2 Rankine cycles: Considerations on forced and mixed convection heat transfer enhancement. (15th September 2016) - Li, Zhouhang; Tang, Guoli; Wu, Yuxin; Zhai, Yuling; Xu, Jianxin; Wang, Hua; Lu, Junfu
Highlights: Heat transfer to supercritical CO2 in IRT was experimentally and numerically studied. Effect of buoyancy on heat transfer relates closely to rib geometry β . When β < 4 deteriorated heat transfer occurs and effect of rib geometries is more obvious. Buoyancy dominates and consistently improves heat transfer for IRT with β > 16. Design strategy for IRT in gas heaters of SCCO2 Rankine cycles was provided. Abstract: To improve heat transfer performance of the gas heater in the supercritical CO2 Rankine cycle, heat transfer characteristics of supercritical CO2 heated in Internally Ribbed Tubes (IRT) was experimentally and numerically investigated over a wide range of buoyancy effect. Experiments reveal that for IRT with a geometric parameter of β = 109, serious local heat transfer deterioration did not occur and buoyancy consistently improved heat transfer. IRT showed far superior performance over smooth tubes. Empirical Nusselt correlations were recommended for both upward and downward flows. A numerical model was then developed and verified against experimental data from IRT with different geometries. Further numerical studies on 7 different IRT demonstrate that buoyancy effect relates closely to rib geometries. For IRT with β = 0.48–4, heat transfer to supercritical CO2 in upward flow was impaired when Bo is around 10 −4, though the impairment became weaker as β increased. When β reached 16, buoyancy-induced impairment disappeared and Nusselt number increased gradually as buoyancy became stronger. Further increase in β up to 109 didn't lead to obvious heat transfer enhancement of supercritical CO2, indicating that rib geometries play a smaller role in heat transfer than buoyancy for IRT with β > 16. Finally, design strategy for IRT was provided for the optimization of gas heaters.